A Bibliometric Analysis of Publication Patterns in Pediatric Neurology - Mitch Wilson; Margaret Sampson; Margaret Sampson; Nick Barrowman; Ewa Sucha; Asif Doja; Asif Doja (Frontiers Media S.A., 2022)
PurposeTo examine the publication patterns of pediatric neurology articles in general pediatric, general neurology, and neurology subspecialty journals using a bibliometric approach.MethodsThe top 5 journals in general pediatrics, general neurology and neurology subspecialties were identified using the 2017 Journal Citations Report (JCR). For general pediatric journals, we selected 4 pediatric subspecialties for comparison of publication patterns with neurology: immunology, endocrinology, gastroenterology, and respirology. For general neurology and neurology subspecialty journals, we searched both the top 5 neurology and neurology subspecialty journals for pediatric articles. Using Ovid Medline, we identified articles published between 2009-2017.ResultsWith regards to child neurology-based articles, 1501 were published in general pediatrics journals, 643 in general neurology journals and 685 in neurology subspecialty journals. Examination of the top pediatric journals revealed that Pediatrics published the most neurology-based articles. Neurology-based studies were published more frequently than other pediatric subspecialty studies. Of the top general neurology Neurology published the most child neurology-based articles, while Epilepsia published the most child neurology-based articles out of neurology subspecialty journals. Cohort studies were the most frequent study type across all journals.ConclusionOur study revealed that child neurology articles are published more often in pediatric journals as opposed to general neurology and neurology subspecialty journals. We also found that in general pediatric journals, neurology-based articles are published more frequently compared to other specialties. Our results provide guidance to authors when considering submission of their pediatric neurology research.